“Wars are won by men not weapons”: the invention of a militarised British settler identity in the Eastern Cape c. 1910–1965 - Ovenstone, Georgina (Department of Historical Studies, 2020)
This thesis is concerned with the invention of South African Anglo identity, and aims to provide a new perspective on how this identity was constructed in the Eastern Cape from c.1910 to 1965. In particular, it considers the ways in which the museum developed to construct South African Anglo identity in the Eastern Cape town of Grahamstown. In the nationalisms of the postcolonial states, independent countries possessed museums in their capitals. These institutions constituted an essential part of national heritage, were crucial for the advancement of education, and operated as a means through which the ‘imagined community’ of the nation state was itself curated and sustained. Postcolonial nationalisms are imagined through the grammar provided by empire. In other words, they are imagined in terms of the administrative and archaeological evidence that colonialism has ‘gathered’ and displayed in its museums. The visual representation of the artefact became a powerful signifier for national identity because of everyone’s awareness of its location in an infinite series of identical symbols. This thesis’s primary focus is on how South African Anglo identity was invented in two key sites in Grahamstown, namely, the school and the museum. It will illustrate how rifles, which were used by the cadet corps at St Andrew’s College, and which were carefully selected and displayed in the 1820 Settlers’ Memorial Museum’s Military Gallery, came to play a central role in symbolizing and militarizing Anglo identity in the eastern province in the twentieth century. In particular, this study will argue that although English identity was reinvented following the 1820 settlers’ centenary in Grahamstown, it was not imagined as a military identity until after the Second World War, and the return of the veterans to St Andrew’s College and the cadet corps. Importantly, it will indicate that the school and the museum comprised key sites through which South African Anglo identity was constructed to reflect images of the British soldier, who in the Eastern Cape, could adapt to local conditions.